How authentic does authentic learning have to be?. Issue 1 (1st January 2018) - Roach, Kate; Tilley, Emanuela; Mitchell, John
Abstract: This study presents an analysis of self-reported student perceptions and experiences of authenticity during an undergraduate first-year problem-based learning (PBL) engineering module at UCL. The aim is to further understand how students perceive authentic learning experiences in order to support and maximise this kind of learning throughout their degree programmes. The data shows that our students did perceive their first-year experiences as authentic despite the fact that the context they worked in and the outputs that they created were not the most real-world part of their experience. The data supports previous work on authentic learning which suggests what really matters is cognitive realism and not physical realism. However, it may be possible to introduce levels of authenticity at increasing levels of complexity throughout the student journey. The analysis is located within the wider field of authentic learning, PBL and builds on this work to suggest how dimensions of authenticity may be graduated across a degree programme.